Edukasi Rasionalitas Penggunaan Herbal Bagi Keluarga Di Padukuhan Karangploso, Desa Sitimulyo, Piyungan , Bantul - Yuliani, Fitri; Handayani, Kiki Rizki (LPPM STIKES Madani, 2026)
This community service program aimed to improve the understanding of families in Karangploso Hamlet, Sitimulyo, Piyungan, Bantul regarding the rational and safe use of herbal medicines. The activity consisted of three stages: health screening (blood glucose and uric acid), health education through a lecture accompanied by leaflet distribution, and an interactive discussion session. The program, held on December 22, 2024, was attended by 33 participants. The health screening results showed that 27% of participants had elevated blood glucose levels, while 57.6% had high uric acid levels. The educational session enhanced participants’ awareness of the principles of rational herbal use, including potential drug–herb interactions and the risks of herbal products containing medicinal chemicals (BKO). Overall, this program provided dual benefits by facilitating early detection of health conditions and improving community health literacy related to the wise use of herbal medicines.